THE EFFECT OF PROCESS INNOVATION ON OPERATIONAL EFFICIENCY OF MSMES: SUPPLY CHAIN INTEGRATION AS A MODERATING VARIABLE - Purnomo, Agus; Khairudin; Yanu Yanuarius Darmawan; Celia Fitriani; Zelfia Irfina; Adi Priyatna (International Journal of Multidisciplinary Reseach, 2026)
Improving operational efficiency is a major challenge for Micro, Small, and Medium Enterprises (MSMEs) amidst business competition and limited resources. Process innovation is often viewed as an internal mechanism capable of increasing efficiency, but previous empirical findings show inconsistent results. This study aims to analyze the effect of process innovation on MSME operational efficiency and examine the role of supply chain integration as a moderating variable. This study uses a quantitative approach with an explanatory research design. Data were collected through a survey of 80 MSMEs in Bandar Lampung City and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that process innovation has a positive and significant effect on operational efficiency. Supply chain integration also has a significant positive effect on operational efficiency. Furthermore, the results of the moderation analysis confirm that supply chain integration significantly weakens the relationship between process innovation and operational efficiency. These findings indicate that the effectiveness of process innovation in improving MSME operational efficiency is highly dependent on the level of supply chain integration. This study makes an empirical contribution to the operations management and supply chain management literature by emphasizing the importance of synergy between internal capabilities and external integration in improving the operational performance of MSMEs in the context of developing countries.